Psychiatric adverse events associated with GLP-1 receptor agonists: a real-world pharmacovigilance study based on the FDA Adverse Event Reporting System database - Chen, Wei; Cai, Peishan; Zou, Wenbin; Fu, Zhiwen (Frontiers in Endocrinology, 2024)
Background: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are widely used due to their profound efficacy in glycemic control and weight management. Within real-world contexts, the manifestation of certain psychiatric adverse events (AEs) has been observed, potentially linked to the administration of GLP-1 RAs. The objective of this study was to undertake a comprehensive investigation and characterization of the psychiatric AEs associated with GLP-1 RAs. Methods: We retrieved AEs reports associated with the treatment of GLP-1 RAs during the period from the first quarter (Q1) of 2004 to Q1 2023 from the FDA Adverse Event Reporting System (FAERS) database. Descriptive analysis was performed to examine the clinical characteristics and time to onset of psychiatric AEs caused by GLP-1 RAs. Moreover, disproportionality analyses were performed using the reporting odds ratio (ROR) to identify GLP-1 RAs-related psychiatric AEs. Results: A total of 8,240 reports of psychiatric AEs were analyzed out of 181,238 adverse event reports of treatment with GLP-1 RAs. Among these cases, a higher percentage of cases were represented by females compared to males (65.89% vs. 30.96%). The median age of these patients was 56 years, with an interquartile range (IQR) of 48–67, based on data available in 286 case reports. This study showed that the median time to onset of overall GLP-1 RAs AEs was 31 (IQR 7-145.4) days, which varied among GLP-1 RAs regimens. Specifically, exenatide had a significantly longer onset time at 45 (IQR 11-213) days, with statistically significant differences from the onset times of the other five GLP-1 RAs (p < 0.0001). Moreover, eight categories of psychiatric AEs including nervousness, stress, eating disorder, fear of injection, sleep disorder due to general medical condition-insomnia type, binge eating, fear of eating and self-induced vomiting, were defined as GLP-1 RAs-related psychiatric AEs through disproportionality analysis. Conclusion: Our findings demonstrate a significant association between GLP-1 RAs and the development of specific psychiatric AEs. Our preliminary findings in this work could provide a better basis for understanding the potential psychiatric AEs that may occur with GLP-1 RAs treatment, assisting clinicians to focus on these AEs and intervene early for optimal risk management.